Lifestyle of students in healthcare programs at the Western Paraná State University (Research, Society and Development, 2024)
Introduction: The constant concern regarding quality of life has prompted the population to seek parameters for disease prevention, thereby arising the need for investigation and the ability to measure elements that characterize an appropriate lifestyle. Objective: To analyze the lifestyle of health area students using the Fantastic Lifestyle Questionnaire (FLQ). Methods: A descriptive, cross-sectional, population-based study was conducted. The sample for this study was convenience-based, consisting of students from the fields of Physiotherapy, Pharmacy, Nursing, Dentistry, and Medicine, from a public institution who agreed to respond to the questionnaire, without distinction of gender or ethnicity. The FLQ comprises 25 questions exploring nine domains related to the physical, psychological, and social components of lifestyle. Results: The study included 82 students, with 39 (47.6%) from the Physiotherapy program, 19 (23.2%) from Pharmacy, 11 (13.4%) from Nursing, 7 (7.3%) from Dentistry, and 6 (8.5%) from Medicine. The mean age was 22.3 years. The overall classification was "Good and Fair," with no participants scoring in the "Needs Improvement" or "Excellent" categories. The domains requiring the most change are related to Nutrition, Safe Sex, and Anxiety. Conclusion: There is evidence suggesting the need for intervention in the quality of life of health science students through educational programs, as well as implementing means to encourage health promotion and improvement in quality of life.